The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21633/jgpha.6.2s18
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting motivations for leaving abusive relationships, substance abuse, and transactional sex among HIV high-risk women

Abstract: Background Women bear a significant burden of the HIV epidemic in the United States. Women classified as ‘HIV high-risk’ often bring co-existing histories of intimate partner violence (IPV), drug use, and transactional sex. To help inform future comprehensive HIV prevention strategies, we aimed to explore common motivating reasons and barriers to leaving and/or terminating engagement in each of these risk-promoting situations. Methods Between August and November 2014, in-depth interviews were conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Regression results provided further evidence of the relationships between transactional sex, drug use, and socioeconomic status. 2,4,5,13,15 In this study, being incarcerated on a property offense (eg, theft) and greater substance use problem severity were associated with an increased likelihood of transactional sex. In a region characterized by widespread poverty, limited employment opportunities, and high rates of substance use, 27,28 incarceration may lead to an even greater economic burden given women's multiple, intersecting disadvantages.…”
Section: Discussionmentioning
confidence: 68%
“…Regression results provided further evidence of the relationships between transactional sex, drug use, and socioeconomic status. 2,4,5,13,15 In this study, being incarcerated on a property offense (eg, theft) and greater substance use problem severity were associated with an increased likelihood of transactional sex. In a region characterized by widespread poverty, limited employment opportunities, and high rates of substance use, 27,28 incarceration may lead to an even greater economic burden given women's multiple, intersecting disadvantages.…”
Section: Discussionmentioning
confidence: 68%
“…National studies conducted in Vitória and João Pessoa revealed that financial dependence, coupled with low schooling and concern with self-support and support of the children, represents an unfavorable scenario for seeking help and, consequently, it is conducive to the permanence of women in the situation of marital violence, not being a specific element for women who use drugs [19][20][21] . Financial subjection to the spouse as an element of vulnerability to living and staying in marital violence has also been identified in studies conducted in the United States, Ethiopia, Nigeria and Kenya [22][23][24][25] .…”
Section: Discussionmentioning
confidence: 96%
“…Estudos nacionais realizados em Vitória e João Pessoa revelaram que a dependência financeira, atrelada à baixa escolaridade e à preocupação com o autossustento e o sustento dos filhos, representa cenário desfavorável para a busca de ajuda e, consequentemente, propício para a permanência das mulheres na situação de violência conjugal, não sendo elemento específico para mulheres que consomem drogas [19][20][21] . A sujeição financeira ao cônjuge enquanto elemento de vulnerabilidade para vivência e permanência na violência conjugal foi também identificada em estudos realizados nos Estados Unidos, Etiópia, Nigéria e Quênia [22][23][24][25] .…”
Section: Discussionunclassified